The use of knowledge management technology among Selangor State government agencies - Nurul Ibtisam Yaacob,; Haniza Othman,; Mokmin Basri,; Hasnuddin Ab Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Knowledge management is one of the important things for the success of an organization. The state of Selangor, which is the first developed state in Malaysia since 2005, often being used as a benchmark by other states, including in terms of information technology implementation. This study has been conducted to identify the use of knowledge management technology among Selangor State government agencies. For this purpose, a quantitative study has been conducted by distributing questionnaire to the respondents from 10 Selangor State government agencies. Studies conducted show that knowledge management technology is part of the instruments used to assist governance in the government agencies of Selangor State. Besides, encouragement from management, related policies and even IT infrastructure are also available and support all information life cycle processes to run well in Selangor State government agencies.